Burden of heart failure attributable to chronic kidney disease in older adults (1990–2021): an analysis from the global burden of disease study - Liu, Wenli; Huang, Lin; Shen, Yaohua; Xu, Lingling; Gu, Wenhua; Lu, Zhaoyu (Frontiers in Public Health, 2025)
BackgroundHeart failure (HF) is a critical global health issue, with chronic kidney disease (CKD) as a significant contributing factor. Both primarily affect older adults, with prevalence rising substantially after age 60. This study examined global trends and disparities in CKD-associated HF among older adults from 1990 to 2021.MethodsUtilizing data from the Global Burden of Disease (GBD) 2021, the study analyzed the prevalence and years lived with disability (YLDs) of CKD-associated HF. Joinpoint regression assessed trends from 1990 to 2021 globally, regionally, and nationally. Health inequity analysis, including the slope index of inequality and health inequality concentration index, evaluated disparities across countries.ResultsFrom 1990 to 2021, the prevalence and YLDs of CKD-associated HF increased globally, with an average annual percentage change (AAPC) of 2.21% [95% confidence interval (CI), 2.17–2.25] and 2.20% (95% CI, 2.16–2.24), respectively. Males exhibited higher prevalence and YLDs but demonstrated a slower increase than females. The low-SDI region exhibited the highest burden, while the high-SDI region showed an unfavorable increase. Socioeconomic disparities were decreased but persisted. From 1990 to 2021, the inequality slope index for prevalence decreased from 143.66 (95% CI, 167.68–119.65) to 114.12 (95% CI, 151.59–76.65), whereas the health inequality concentration index improved from −0.21 (95% CI, −0.30 to −0.12) to −0.07 (95% CI, −0.14 to 0) for prevalence.ConclusionThe global burden of CKD-associated HF has increased substantially, with persistent disparities across gender and SDI levels. Strengthening preventive measures and implementing effective interventions are essential to addressing this escalating health challenge.